Empirical Evidence for Broadband as a Skills-Biased Technology - Coville, Aidan; Fernandez, Chloe Monica; Mannava, Aneesh; Piza, Caio; Raja, Siddhartha (World Bank, Washington, DC, 2020)
We exploit time and region variation in broadband availability in Georgian villages (settlements) to test whether high speed broadband is a skill-biased technological shock. We use an annual, nationally representative firm survey in Georgia from 2006 to 2014 and exploit the non-random phased rollout of broadband internet across the country to estimate impacts of broadband availability on firm performance outcomes and wage inequality using a difference-in-differences approach. Our main findings suggest that impacts are consistent with broadband being a complement to initial endowments. We find positive effects on firm revenues and wages but these effects are restricted to firms from settlements that lie in the upper half of average revenue distribution. We find similar results when disaggregating impacts by the average wage distribution. Our findings are consistent with ICT being skills-biased given the positive effects on average wages and profits and some indication that firms substituted lower- for higher-skilled workers. Our results point to an increase in the existing wage gap between the top and bottom half of the wage distribution but suggest that broadband availability helped shrink the baseline wage gap between treated and control settlements.